STRENGTHENING NATIONAL ECONOMIC GROWTH AND EQUITABLE INCOME THROUGH SHARIA DIGITAL ECONOMY IN INDONESIA - Barata, Amrin (Journal of Islamic Monetary Economics and Finance, 2019)
The rapid progress of information and communication technology (ICT) creates a new look of the Indonesian economy, transforming from the conventional economy into a digital economy. The part of the digital economy currently developing worldwide, include in Indonesia is, Fintech (Financial Technology) and E-commerce. Additionally, Indonesia contributes to 4 percent of total e-commerce sales around the world. The development of Fintech in Indonesia is still at early stages, as many industries have not developed such a practice. Besides, there are many opportunities that have not been explored to its full potential. The research employs Input Output (I-O) analysis, using shock of IDR 3.90 trillion in investment of the sharia e-commerce subsector, we found through this study that the national economic growth grew by 0.048 percent or the economic output increased by IDR 5.08 trillion. As for the impact on gross value added (GVA) grew by 0.072 percent or increased by IDR 3.72 trillion. In addition, national labor income increased by IDR 795.36 billion with investment in sharia e-commerce subsectors. After an additional shock to the Fintech and the trade sector, economic growth increased by 0.052 percent or IDR 5.48 trillion. Sharia e-commerce and sharia Fintech should be able to have a big impact on the economic growth, increasing the amount of labor needed so that it can absorb more national labor. Thus, economic growth, increased income, and job creation will potentially reduce poverty and inequality in that the implications in the long term will further strengthen sustainable national economic growth.